2019
DOI: 10.1177/0885066619842537
|View full text |Cite
|
Sign up to set email alerts
|

Extended Indications for Extracorporeal Membrane Oxygenation in the Operating Room

Abstract: Background: The use of extracorporeal life support (ECLS) for cardiorespiratory support is increasing. Traditional absolute contraindications are currently deemed relative contraindications. Extracorporeal life support is now considered for a wider cohort of patients on a case-by-case basis. Method: We performed a review of the literature and examined current Extracorporeal Life Support Organization guidelines that support the use of ECLS in the operating room, based on the underlying pathology and surgical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…OLV resulted in severe cardiopulmonary complications in almost one-third of our patients, including four patients who required CPR. Two patients did not tolerate OLV at all, and one patient received ECMO, which may be an emergency option for tracheal surgery when OLV is not possible [12, 13]. Transient hypoxemia in OLV is a common complication, and fiber-optic monitoring of tube position, adjustment of ventilation strategy and increasing the FiO 2 prevent longer episodes [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…OLV resulted in severe cardiopulmonary complications in almost one-third of our patients, including four patients who required CPR. Two patients did not tolerate OLV at all, and one patient received ECMO, which may be an emergency option for tracheal surgery when OLV is not possible [12, 13]. Transient hypoxemia in OLV is a common complication, and fiber-optic monitoring of tube position, adjustment of ventilation strategy and increasing the FiO 2 prevent longer episodes [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of ECMO-assisted noncardiac thoracic procedures is becoming more and more attractive. 8 While conventional CPB systems can provide an ideal operative environment for challenging cases, ECMO circuits cause less coagulopathy, inflammation, and vasoplegia due to the absence of cardioplegia, a reservoir outside the body and flexible approaches. 9,10 Complex tracheobronchial, atrial, or combined lung-aortic resections constitute a challenging operating field for the thoracic surgeon and the use of an extracorporeal assistance as respiratory or circulatory support could facilitate stable intraoperative conditions for fulfilling the main goal of complete (R0) resection.…”
Section: Discussionmentioning
confidence: 99%
“…11 Use of ECMO as total respiratory support for complex tracheobronchial resections has been described previously. 8,11,12 Klepetko et al reported a series of 10 patients undergoing complex carinal, tracheobronchial resections utilizing VA-ECMO with excellent results in terms of mortality (0%) and complete resection (89%). In our collective of carinal resections (n ¼ 8) complete resection (R0) rate was lower (78%) and 30-day mortality was higher (25%).…”
Section: Discussionmentioning
confidence: 99%
“…Although cancer is traditionally considered as one of the contraindications for extracorporeal membrane oxygenation (ECMO) 16 , considering the increasing survival rate and the fact that patients with cancer represent a considerable portion of IHCA cases, it is reasonable to consider implementing ECPR in these cases, particularly based on advance directives and anticipated life expectancy. While some studies have shown increased survival of patients with cancer using ECMO or extracorporeal life support (ECLS), the majority are targeted to paediatric patients, hematologic malignancies, or acute respiratory failure without cardiac arrest 17 – 21 ; therefore, it remains unclear whether ECPR could benefit patients with cancer who suffer IHCA.…”
Section: Introductionmentioning
confidence: 99%